Современная эпоха техногенной цивилизации – время возможной победы над старением и смертью - Vishev I. V. (Priority directions of scienceand education development, 2016)
The background of a solution of the problem of change of the head, especially its present stage connected first of all with names Sergio Canavero and Ren of Xiaoping, and also Elisabeth Parrish's experiment for the purpose of a victory over aging and preservation of youth is briefly considered. Thereby transition to an immortogumanizm or bessmertnichesky humanity, - consistently optimistic form of modern humanity is carried out.
Keywords: клонирование; техногенная цивилизация; время оптимизма; пересадка головы; имплантация генетического материала; практическое бессмертие человека; восстановление человеческой жизни; иммортогуманизм; technogenic civilization; optimism time; change of the head; cloning; implantation of genetic material; practical immortality of the person; restoration of human life; immortogumanizm